Competitive mountain bike and road cycling: physiological characteristics of athletes and demands of competition - Lee, H. (2003)
Despite many studies describing the physiological characteristics of professional road cyclists and recent work describing the demands of competition, there is a paucity of similar information regarding elite mountain bike (MTB) cyclists. The aim of the present work was to describe the physiological characteristics and the demands of competition for successful MTB cyclists relative to successful road cyclists. Internationally competitive cyclists from both disciplines (seven MTB and seven road) completed the following laboratory tests: anthropometric measurements, an incremental cycle ergometer test and a 30 minute laboratory time trial. In addition, the power output profile obtained in the field from a world-class MTB cyclist riding a simulated race were compared to successful road cycling performances (placing top 3) in flat (FLAT), semi-mountainous (SEMO), high-mountainous (HIMO), individual time trial (ITT) and criterium (CRIT) road races. Due to conversion problems, 6 sentences have been omitted. For full abstract, see 01front.pdf. These results indicate that success in international MTB racing requires high power-to-weight characteristics complemented by a light and lean physique. MTB racing is associated with greater torque at the pedal crank, a more constant effort with less time at lower power outputs and a higher frequency of highintensity surges than road racing. Therefore coaches should take into account these unique MTB racing characteristics when devising training programs for elite athletes.